Baseline characterization of aquaculture systems and livelihoods in Nasarawa– Nigeria. Hatacheries dataset - Manyise, Timothy; Lozano, Denise; Ghazali, Saadiah; Roslan, Shazleen (2023)
This study was conducted to understand how fish seed is produced and disseminated to different actors including traders and farmers.